Short-term Survival of Acute Respiratory Distress Syndrome Patients at a Single Tertiary Referral Centre in Indonesia - Zulkifli Amin; Hasna Afifah; Chrispian Oktafbipian Mamudi (Acta Medica Indonesiana, 2017)
Aim: to identify the 28-day short-term survival rate in patients with acute respiratory distress syndrome (ARDS). Methods: this is a retrospective cohort study conducted at a tertiary referral hospital in Jakarta, Indonesia. We conducted the study for 10 months and data was extracted from medical records between October 2015 and August 2016. The primary end point of the study was 28-day short-term survival rate using the initial date of ARDS diagnosis as the index time. Overall survival rate was analyzed using Kaplan-Meier test and multivariate Cox regression analysis. Results: there were 101 ARDS subjects during 10 months of study. The overall rate of  28-day survival was 47.5% and the median time of survival was 10 days (95% CI 2.47–17.52). The survival rate in ARDS patients was reduced significantly at the first week after the diagnosis of ARDS was made, which indicated that the highest mortality occured in the first week. Subjects with APACHE II score of >20 had a hazard ratio (HR) of 2.45 (95% CI 1.40-4.28) and those with moderate-severe of ARDS had HR of 2.27 (95% CI 1.25-4.12). Conclusion: the short-term survival rate of ARDS in developing countries  including Indonesia is still low and early management with optimal treatment provided within the first week may improve the survival rate.